News About Persons (Academy of Management Journal, 1969)
The article reports on several promotions among business college professors. Phil Carroll has been appointed as a member of the International Academy of Management. Dr. Lawrence S. Hill, Leslie E. This and Dr. William Glueck have received promotions.